Computational reconstruction and characterization of ancestral proteins relevant to prokaryotic-eukaryotic transition 2 billion years ago - Pulido, Ma. Angelica S. (Transactions of the National Academy of Science and Technology, 2011)
Anaphase Promoting Complex 11, most probable ancient Ubiquitin ligase is correlated with a former study to have emerged after the great Oxidation Event. RPN3, most ancient non-ATPase 26S proteasome lid appeared in cyanobacteria and proteobacteria emergence. However, BCS1 in mitochondria inner membrane, found to be the most ancient protein, functions as an ATP- dependent chaperone which led to some rise of multicellular organisms. The AA sequences of these genes were retrieved with Entrez gene in FASTA format and aligned with CLUSTALW via MEGA 4. Using gamma distribution and JTT matrix rates, distance matrices were obtained and used to create a phylogenetic tree. The ancestral sequences were generated in the codeml program of PAML. ProtParam and SWISS_MODEL were used in characterizing the 1ᵒ, 2ᵒ, and 3ᵒ structures of derived ancestral proteins and reference species. Using ProtParam, physico-chemical properties of Ub ligase, mitochondrial chaperones and proteasome were known. Visualization of the 3-dimesional structures of these ancestral proteins was requested from SWISS MODEL and Rasmol. New Likelihood-based Probability Method gave 0.91, 0.86, and 0.73 for all, variable, and parsimony-informative sites, respectively, whereas the corresponding probabilities for the parsimony method were 0.84, 0.76, and 0.51, respectively. The probability that ancestral sequence was correctly reconstructed ranged from 91.3 to 98.7%.